2017
DOI: 10.3390/ijms18030456
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of Dysregulated MicroRNA in Type 2 Diabetes Mellitus

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that modulate the cellular transcriptome at the post-transcriptional level. miRNA plays important roles in different disease manifestation, including type 2 diabetes mellitus (T2DM). Many studies have characterized the changes of miRNAs in T2DM, a complex systematic disease; however, few studies have integrated these findings and explored the functional effects of the dysregulated miRNAs identified. To investigate the involvement of miRNAs in T2DM, we obtained and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
83
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 102 publications
(119 reference statements)
10
83
0
5
Order By: Relevance
“…MicroRNAs are small noncoding RNAs composed of 21-23 nucleotides that act as the key regulators of gene expression and biological processes (He et al, 2017). Previous studies have *Author for correspondence: Shirin Shahbazi, Department of Medical Genetics, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are small noncoding RNAs composed of 21-23 nucleotides that act as the key regulators of gene expression and biological processes (He et al, 2017). Previous studies have *Author for correspondence: Shirin Shahbazi, Department of Medical Genetics, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Of the 57 miRNAs showing concentration differences between the progressor and non-progressor groups, 26 of them (miR-10b-5p, miR-144-3p, miR-451a-5p, miR-192-5p, miR-125b-5p, miR-101-5p, miR-122-5p, miR-150-5p, miR-17-3p, miR-193a-5p, miR-193b-3p, miR-29c-5p, miR-320a-3p, miR-320b-3p, miR-550a-3p, miR-100-5p, miR-10a-5p, miR-181a-3p, miR-190a-5p, miR-136-5p, miR-375-3p, miR-487b-3p, miR-7-5p, miR-210-3p, miR-378a-3p, and miR-99a-5p) have been previously described as being associated with T2DM based on our recent meta-analysis of the field. 10 We selected 14 miRNAs for qRT-PCR validation and were able to confirm the concentration changes for 10 of these miRNAs (miR-122-5p, miR-127-5p, miR-192-5p, miR-210-3p, miR-3200-3p, miR-375-3p, miR-376b-3p, miR-4532-5p, and miR-660-3p, and miR-7641-3p). Some miRNAs could not be verified with qRT-PCR, probably due to the specific qPCR platform used and high-false negative rate associated with qRT-PCR as previously reported.…”
Section: Log 2 Fc (> 15 Fold Change P-value B-h Fdrmentioning
confidence: 99%
“…It is also showed that miR-335 upregulation promoted defective initiation of insulin vesicles, resulting in impaired insulin secretion [27]. As for the part of miR-765 regulating diabetes, a study observed an enrichment of miR-765 in T2D [28]. To grasp more molecular evidence for T2D development, we here examined the role of miR-765 in this area as well as its interaction with PDX1.…”
Section: Introductionmentioning
confidence: 98%